2017
DOI: 10.1111/bph.13920
|View full text |Cite
|
Sign up to set email alerts
|

l‐Homocysteine‐induced cathepsin V mediates the vascular endothelial inflammation in hyperhomocysteinaemia

Abstract: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…CTSV mediates inflammation in HUVECs by upregulating these cytokines. 92 LGALS1 binds to membrane glycoproteins, inhibiting their endocytosis and cathepsin-mediated cleavage, 93 while cathepsins induce LGALS1 in endothelial cells during angiogenesis. 94 Whether decreased expression of cathepsin targets in AMR is due to higher cleavage and higher HLA-presentation requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…CTSV mediates inflammation in HUVECs by upregulating these cytokines. 92 LGALS1 binds to membrane glycoproteins, inhibiting their endocytosis and cathepsin-mediated cleavage, 93 while cathepsins induce LGALS1 in endothelial cells during angiogenesis. 94 Whether decreased expression of cathepsin targets in AMR is due to higher cleavage and higher HLA-presentation requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the T allele carriers of the rs1801133 polymorphism, the function of MTHFR may be affected since the normal alanine residue is replaced by a valine residue in the polypeptide, which in turn affects the production of 5-MTHF and the remethylation of homcysteine, resulting in elevated plasma homosysteine levels. Studies have shown that homocysteine is a risk factor for CAD, and oxidative stress [ 33 ], vascular inflammation [ 34 ] and endothelial injury [ 35 ] are involved in the underlying mechanisms in which homocysteine causes CAD. All these events are likely to trigger the development of atherosclerosis and arterial thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine (Hcy) is a natural amino acid generated by the body’s methylation process. It is well known that hyperhomocysteinemia has become an important risk factor for cerebrovascular diseases in the general population (Leng et al, 2017 ). On the other hand, the toxic effects of Hcy on dopaminergic neurons have been confirmed in vitro and in vivo experiments (Kocer et al, 2016 ).…”
Section: Biochemical Biomarkersmentioning
confidence: 99%